Short-chain Fatty Acids Inhibit Staphylococcal Lipoprotein-induced Nitric Oxide Production in Murine Macrophages - Park, Jeong Woo (Immune Netw, 2019)
Staphylococcus aureus, a Gram-positive pathogen, can cause severe inflammation in humans, leading to various life-threatening diseases. The lipoprotein is a major virulence factor in S. aureus-induced infectious diseases and is responsible for excessive inflammatory mediators such as nitric oxide (NO). Short-chain fatty acids (SCFAs) including butyrate, propionate, and acetate are microbial metabolites in the gut that are known to have anti-inflammatory effects in the host. In this study, we investigated the effects of SCFAs on S. aureus lipoprotein (Sa.LPP)-induced NO production in mouse macrophages. Butyrate and propionate, but not acetate, inhibited Sa.LPP-induced production of NO in RAW 264.7 cells and bone marrow-derived macrophages. Butyrate and propionate inhibited Sa.LPP-induced expression of inducible NO synthase (iNOS). However, acetate did not show such effects under the same conditions. Furthermore, butyrate and propionate, but not acetate, inhibited Sa.LPP-induced activation of NF-κB, expression of IFN-β, and phosphorylation of STAT1, which are essential for inducing transcription of iNOS in macrophages. In addition, butyrate and propionate induced histone acetylation at lysine residues in the presence of Sa.LPP in RAW 264.7 cells. Moreover, Sa.LPP-induced NO production was decreased by histone deacetylase (HDAC) inhibitors. Collectively, these results suggest that butyrate and propionate ameliorate the inflammatory responses caused by S. aureus through the inhibition of NF-κB, IFN-β/STAT1, and HDAC, resulting in attenuated NO production in macrophages.